Stalking behavior and high-functioning autism spectrum disorders – a case report - Ventura, Fabiana (The journal of forensic psychiatry & psychology, 2022)
The prevalence of autism spectrum disorders (ASD) is increasing, and the correlates of involvement of this population in the criminal justice system have been reported. People with ASD have specific deficits such as difficulties in social communication and behavior, impulsivity, misinterpretation of rules, obsessions, and restricted interests, increasing their vulnerability to becoming victims and offenders. Herein, we report the case of a male 40 high-functioning ASD patient accused of stalking. This paper highlights clinical and forensic challenges when assessing patients with ASD prosecuted for stalking behaviors.